10 kHz High‐Frequency Spinal Cord Stimulation for Chronic Axial Low Back Pain in Patients With No History of Spinal Surgery: A Preliminary, Prospective, Open Label and Proof‐of‐Concept Study. Issue 1 (26th December 2016) - Al‐Kaisy, Adnan; Palmisani, Stefano; Smith, Thomas E.; Pang, David; Lam, Khai; Burgoyne, William; Houghton, Russell; Hudson, Emma; Lucas, Jonathan
Abstract : Objective: To explore the effectiveness of 10 kHz high frequency spinal cord stimulation (HF10 therapy) treatment of chronic low back pain in patients who have not had spinal surgery. Methods: Patients with chronic low back pain without prior spinal surgery were evaluated by a team of spine surgeons to rule out any spinal pathology amenable to surgical interventions and by a multidisciplinary pain team to confirm eligibility for the study. After a successful (>50% back pain reduction) trial of HF10 therapy, enrolled subjects underwent permanent system implantation and were followed‐up one year post‐implant. Results: About 95% of the enrolled subjects (20/21) received the permanent system. At 12 months post‐implant, both back pain VAS score and ODI were significantly reduced compared with baseline values (by 73% and 48%, respectively); an estimated quality‐adjusted life year gain of 0.47 and a reduction in opioid use by 64% was observed. Four more patients among those unable to work at baseline due to back pain were employed at 12 months post‐implant. There were no serious adverse events. Conclusion: HF10 therapy may provide significant back pain relief, reduction in disability, improvement quality of life, and reduction in opioid use in chronic low back pain not resulting from spinal surgery.